6th FEB International Scientific Conference: Challenges in Economics and Business in the Post-COVID Times (University of Maribor Press, 2022)
The Proceedings of the 6th International Scientific Conference, organised by the University of Maribor’s Faculty of Economics and Business under the umbrella theme “ Challenges in Economics and Business in Post-Covid Times”, brings together 52 contributions from authors across 18 countries. Individual articles address selected issues regarding the impact of the COVID-19 epidemic on the functioning of society and changes in the economic and business environment, as well as how society and organisations have dealt with the changed social conditions following the epidemic. In the articles, the authors present various aspects of the impact of the COVID-19 epidemic on the functioning and behaviour of society’s stakeholders and the necessary changes in how they function, given the social conditions present following the end of the epidemic. The contributions also present the social experience of dealing with COVID-19, and offer possible solutions for the macroeconomic and business operations of society and organisations in a post-epidemic context.